2017
DOI: 10.1055/s-0042-124187
|View full text |Cite
|
Sign up to set email alerts
|

Neugeborenenscreening auf Mukoviszidose in Deutschland: Vergleich des neuen Screening-Protokolls mit einem Alternativprotokoll

Abstract: Zusammenfassung Hintergrund Zur Einf?hrung des Neugeborenenscreening auf Mukoviszidose (CF) in Deutschland hat der Gemeinsame Bundesausschuss (G-BA) ein neues Screeningprotokoll mit der Bestimmung von Immunreaktiven Trypsinogen (IRT) als ersten und Pankreatitis assoziierten Protein (PAP) als zweiten Schritt eingef?hrt. In einem dritten Schritt folgt eine Analytik von 31 CFTR-Mutationen, um den positiven Vorhersagewert (PPV) gegen?ber einem rein biochemischen IRT/PAP-Protokoll zu erh?hen. Methoden Der Datenpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…For example, there is currently no modern CF NBS protocol in which a sample is considered positive after an ultra-high IRT alone. Furthermore, it was shown that, as previously expected, only about 25% of CF patients diagnosed with this protocol received a search for CFTR mutations during the CF NBS protocol [26]. Based on data from the Heidelberg IRT/PAP+SN pilot study, the sensitivity of the protocol was estimated to be 96% in the post hoc analysis mentioned above [26].…”
Section: Current Pap-based Cf Screening Protocols In Usementioning
confidence: 70%
See 2 more Smart Citations
“…For example, there is currently no modern CF NBS protocol in which a sample is considered positive after an ultra-high IRT alone. Furthermore, it was shown that, as previously expected, only about 25% of CF patients diagnosed with this protocol received a search for CFTR mutations during the CF NBS protocol [26]. Based on data from the Heidelberg IRT/PAP+SN pilot study, the sensitivity of the protocol was estimated to be 96% in the post hoc analysis mentioned above [26].…”
Section: Current Pap-based Cf Screening Protocols In Usementioning
confidence: 70%
“…Furthermore, it was shown that, as previously expected, only about 25% of CF patients diagnosed with this protocol received a search for CFTR mutations during the CF NBS protocol [26]. Based on data from the Heidelberg IRT/PAP+SN pilot study, the sensitivity of the protocol was estimated to be 96% in the post hoc analysis mentioned above [26]. A complete evaluation of the CF NBS protocol used in Germany is now scheduled to be conducted after 3 years of application.…”
Section: Current Pap-based Cf Screening Protocols In Usementioning
confidence: 84%
See 1 more Smart Citation
“…The frequency of variants and genotypes in the general population should be considered to evaluate the risk of a particular genotype to cause clinical CF; in other words, the penetrance of clinical CF in individuals carrying a given genotype. This was previously shown to be very low for R117H [ 59 ], an observation which led to its withdrawal from NBS variant panels [ 27 , 32 ], and, more recently, for the T5 variants and other variants commonly identified in inconclusive cases [ 60 ]. Such epidemiological data emphasize the importance of documenting the penetrance of variants before widely implementing EGA in core NBS programs.…”
Section: Values and Challenges Of Cftr Extendedmentioning
confidence: 99%
“…Dagegen hat das letztere Protokoll, welches als post-hoc Analyse ausgewertet wurde und nunmehr als Publikation vorliegt, eine CF-Positivität erst nach dem zweiten und dritten Schritt der Messung des PAP-sowie der DNA-Analytik bewertet. Als bedeutsamste Unterschiede in den beiden skizzenhaft dargelegten Vorgehensweisen (für die ausführliche Darstellung wird auf das Manuskript der Heidelberger Gruppe verwiesen [6]) fanden sich folgende Daten:…”
unclassified